Total body mapping in the follow-up of melanocytic lesions: recommendations of the Brazilian Society of Dermatology - Carlos Barcaui; Renato Marchiori Bakos; Francisco Macedo Paschoal; Flávia Vasques Bittencourt; Bianca Costa Soares de Sá; Hélio Amante Miot (Sociedade Brasileira de Dermatologia, 2021)
Abstract Total body mapping comprises photographic documentation of the entire body surface followed by digital dermatoscopy of selected melanocytic lesions, aiming to compare their evolution over time and identify new lesions. As this is an exam based on comparative analysis of serial dermoscopic body images, standardization of the technique for performing total body mapping is essential. Prepared by specialists from the Brazilian Society of Dermatology, using the modified Delphi method, this article provides recommendations for carrying out total body mapping in Brazil, regarding its indications, technical aspects, and the issuing of the report.